Catatan Pendidikan Indonesia: Evaluasi, Solusi, & Ekspektasi - Siva Aprilyanti; Masduki Asbari; Alfiana Supriyanti; Ica Alfiatun Fadilah (AGUSPATI RESEARCH INSTITUTA, 2024)
The purpose of this discussion is to evaluate the opportunities and potential of education in Indonesia in the future. So that we can achieve optimal learning outcomes and not be left behind by other countries, contributions from the community and government are really needed for Indonesian education. This research report uses a descriptive qualitative method by taking notes because the data source was obtained by listening to the oral narrative from the Satu Persen - Indonesian Life School Youtube channel entitled